Could health-improving interventions address the growing unemployment crisis?. (March 2021) - Butler, Joseph
SUMMARY: The COVID-19 pandemic is causing unprecedented rates of unemployment. Poorer mental health is a cause and a consequence of unemployment, and job seekers with poorer mental health remain unemployed for longer. The review in this month's Cochrane Corner aimed to evaluate the effects of health-improving interventions on job seeker's re-employment rates. This commentary critically evaluates the review and explores the relevance of its findings.